Hygrophila R. Br. (Acanthaceae) no Cerrado Goiano: história, taxonomia e potencialidades - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
The Acanthaceae family stands out as one of the most diverse groups of angiosperms in tropical regions, yet remains underrepresented in floristic surveys of the Brazilian Cerrado. This dissertation investigates the genus Hygrophila R. Br. (Acanthaceae) in the state of Goiás through an interdisciplinary approach that integrates historical botany, phytochemistry, taxonomy, and pollen morphology. In the first chapter, historical documents enabled the rediscovery of Hygrophila humistrata Rizzini, an endemic species from the Cerrado of Goiás previously known only from its type series collected in 1952. Morphological and palynological analyses of the rediscovered material revealed incongruences with its originais generic placement, supporting a new taxonomic combination to be proposed in a separate publication. The second chapter presents the phytochemical screening of H. guianensis and H. humistrata, as well as the partial composition of the essential oil of the latter, revealing secondary metabolites with pharmacological potential. The third chapter provides a taxonomic treatment of Hygrophila species in Goiás, supported by palynological analyses that highlight consistent differences between H. costata and H. guianensis. Phenological patterns, distribution maps, in situ photographs, illustrations, and scanning electron micrographs of pollen grains are also provided. The integration of multiple disciplines enabled the rediscovery of neglected species, unveiled their bioactive potential, and clarified taxonomic boundaries through morpho-palynological evidence. This interdisciplinary strategy deepens the ecological understanding of the group and underscores the value of integrated conservation efforts, particularly in highly threatened biomes such as the Cerrado
Hygrophila R. Br. (Acanthaceae) in the Cerrado of Goiás: history, taxonomy, and potentialities
Keywords: Botânica histórica – Cerrado goiano; Botânica – Taxonomia – Lamiales; Botânica – Prospecção – Cerrado goiano; Fitoquímica – Cerrado Goiano; Lamiales - Bioprospecting - Biodiversity; CIENCIAS HUMANAS::GEOGRAFIA; BOTANICA::FITOGEOGRAFIA